PENGUJIAN EFEKTIVITAS EKSTRAK CAPSICUM ANNUUM SEBAGAI ANTI INFLAMASI PADA TIKUS WISTAR YANG DIINDUKSI CCL4 - Aldian Mulyanto Lokaria; Berliana Islamiyarti Hydra; Zelly Dia Rofinda (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2018)
Background: Inflammation has a major role in the pathogenesis of various diseases. Non steroidal anti inflammatory drugs (NSAIDs) being the most often used drug in community, but prolonged use NSAIDs can cause digestive problems and other side effects. Capsaicin from red chilli (Capsicum annuum) extract have anti-inflammatory effects and as a replacement candidate of NSAIDs. Methods: This research is an experimental research with pre and post test design for differential count and post test only design to leukocytes count and erythrocyte sedimentation rate (ESR). The four positive control groups and treatment group contains 5 samples of wistar rat for each group induced by CCl4 2% 0,5 ml/day for 30 days. After induction, the samples were given treatment for 14 days with ad libitum standard diet (negative control); aspirin; acetaminophen; ibuprofen; mefenamic acid (positive control), and extracts of C. annuum 2% (treatment group). Results: The differential count from extracts of C. annuum 2% group showed a decrease in lymphocytes (p <0,001) than before treatment. While the results of leukocytes count and ESR from C. annuum extract 2% group showed smaller results, ie 5.020 ± 2.071 (p = 0,209) and 2,00 ± 1,26 (p = 0,174) compared to the NSAIDs groups. Conclusion: Extract of C. annuum 2% were able to decrease the proportion of lymphocytes significantly, but the reduced of leukocytes count and ESR unsignificantly.